Invasive carcinoma of the cervix in young women : a controlled study (1974-1983) including re-examination of the histology and cytology for evidence of human papillomavirus infection - Jennings, O G N (Department of Obstetrics and Gynaecology, 2017)
Invasive carcinoma of the cervix was compared in women under and over 35 years of age in a 10-year cohort study for the period 1974 - 1983. The aim was to determine if there were any significant differences in disease characteristics and survival. A non-concurrent prospective study design was employed with a follow-up period of at past 5 years. All eligible young patients (n = 82) were studied out of a total patient population of 1522 and compared with a 13% random sample (n = 82) of equally eligible older patients. There were three study losses in each group (3,7%), giving a final comparison number of 79. Patient data included disease stage, treatment type and complications, recurrence time and site and survival time. Tumour pathological characteristics were reviewed and evidence of Human Papillomavirus (HPV) was sought on histology and cytology specimens. Life table analyses were performed on the survival data and compared by the logrank test. The covariates of disease stage, treatment type and tumour type were included in the analysis of the effect of age group on survival. Multivariate analysis with a proportional hazards general linear model was performed for simultaneous control of confounding factors. Other disease characteristics were compared using the Chi-square test. The overall proportion of young women was 11,6%. (This did not change for the period 1984 1988.) Five-year survival was 57% for the young and 46% for the older group (not statistically significant: p = 0,198). There was no statistically significant difference in a number of characteristics, including tumour size, endocervical site, grade or type. There were 8 non-squamous tumours in the young {10%). Residual disease, time to recurrence, rate and site of distant metastasis, and treatment of recurrent tumour did not differ significantly; nor did rate of spread to lymph nodes, adequacy of follow-up or treatment complications. Evidence of HPV was found in 35% of evaluable histology and 21% of malignant cytology. There was no significant excess of HPV in the young group. The same applied to the length of the preinvasive phase and the false negative cytology rate - no significant differences were found. There were significantly more Stage lB tumours in the young group (p = 0,01), surgery was used more often for treatment in young patients (p = 0,027) and the difference in survival between the disease stages was highly significant (p 0,0001). Multivariate analysis showed that the effect of age on survival was non-significant (p = 0,850). The conclusion of the study is that cervical carcinoma in young women is not a different disease with a worse prognosis than in older women. Furthermore, it is not becoming more common in the young locally. Young women tend more often to have early stage disease.